(untitled) (Philological Studies, 2021)
The paper presents the mutual translation of Slovenian and Macedonian children’s poetry from the end of the Second World War to the present day. The first part of the paper presents data on book translations of Slovenian children’s poetry into Macedonian and Macedonian children’s poetry into Slovene in two stages: the first one shows translations in the period between 1945 and 1990, when Slovenia and Macedonia were part of the common state of Yugoslavia, and the second one shows translations published after independence, i.e., between 1991 and 2020. The proportion of mutual translations of Slovenian and Macedonian children’s poetry compared to translations of children’s prose and drama is also shown. In the second part, the rare book translations of Slovenian youth poetry into Macedonian and Macedonian into Slovenian published after 2000 are analysed using a functional approach. The analysis seeks to show whether the translated text matches the illustrations, whether the form and sound of the poems are preserved, and what the transfer of the vocabulary is like. The conclusion suggests possibilities for more active intercultural c mediation in this field.